PENGARUH PENAMBAHAN EKSTRAK BUAH MENGKUDU (Morinda citrifolia Linn) DALAM PENGENCER TERHADAP MOTILITAS SPERMATOZOA PADA SEMEN CAIR SAPI BALI - Sahiruddin Sabile; Abdul Latief Toleng; Muhammad Yusuf; Zulkharnaim -; Sri Firmiaty; Muhammad Idrus; Nasriyanto - (AVES: Jurnal Ilmu Peternakan, 2016)
The processing of liquid cement is likely to decrease sperm motility. It can be caused by the oxidative reaction to increase the amount of free radicals. Noni (Morinda citrifolia Linn) contains many antioxidants that can serve counteract free radicals. This study aims to determine the addition of extracts of noni (Morinda citrifolia Linn) in order to maintain the individual motility of spermatozoa in the semen liquid Bali cattle. This research was conducted at the Laboratory of Animal Reproduction Semen Processing Unit Faculty of Animal Husbandry Hasanuddin University Makassar. Extracts of noni fruit (Morinda citrifolia Linn) effect on sperm motility (P <0.05). Storage P0 at 3 h to day 2 showed higher motility. Concentration 0,02 gr/ml (P1) gives the best results in maintaining sperm motility on day 3rd to 5th. Extracts of noni fruit (Morinda citrifolia Linn) can retain sperm motility because many contain many antioxidants that serve to neutralize free radicals cause a decrease in sperm motility during equilibration at 5 0C.